Review of Malaysian social media influencers credibility/ Nur Anis Atira Norazman ... [et al.] - Norazman, Nur Anis Atira; Abdullah, Anwar Fikri; Mohd Shuib, Ahmad Sofiyuddin; Mohd Pahme, Nur Faizah; Sulaiman, Mohamad Zaidi (Universiti Teknologi MARA, Perak, 2023)
This review study delves into the self-promotion strategies of social media platforms, particularly focusing on the realm of influencer's criteria that are credible for the Malaysia market. The primary objective of this research is to enlighten marketers about existing Influencer's Criteria guidelines with insights into effectively identifying credible influencers for promoting their brands. Employing qualitative methodologies, the research employs techniques such as content analysis, case studies, and observation of promotional video content. The investigation centres around five Instagram influencers from Malaysia, examining their advertising approaches, alignment with specific niches, and the categories of content they share. The findings underscore the paramount importance of various factors in influencer selection, including relevance, authenticity, engagement, reach, content quality, brand alignment, and a proven track record. Furthermore, the research delves into the array of video content that influencers employed. Armed with an understanding of how influencers present themselves and the characteristics that define influential individuals, marketers are equipped to mitigate the risks associated with influencer marketing fraud and establish fruitful collaborations that resonate with their brands.